Perceptions on Sprekelia formosissima (L.) Herb. as an ornamental plant in Puebla and Morelos - Salomé Castañeda, Edith; Mayett Moreno, Yésica; Rodríguez Piñeros, Sandra; Flores Alonso, Daniel Alberto; Cavazos Arroyo, Judith (Revista Mexicana de Ciencias Agrícolas, 2018)
According to the inventory made by the ornamental network, Mexico is one of the richest countries in genetic resources and has 4 220 species used as ornamental or potential to be introduced to the ornamental horticulture. One of these is Sprekelia fomosissima known as Aztec lily, grows wild in Mexico City, State of Mexico, Morelos and Puebla, among other States. Mexico has not developed its production, largely due to ignorance of their horticultural benefits, because of the producers, marketers and consumers as well. In the international market is sold in some nurseries in Europe and USA, so it follows that possibilities would be placed on the national market. This study aimed to assess the level of knowledge, perception and willingness to buy and sell the Azteca Lily by potential consumers of ornamental plants in nurseries in the cities of Atlixco, Puebla and Cuautla, Morelos, as well as disclosing its importance and use as an ornamental plant. We applied 357 surveys during the months of April and May, 2013. Lily Azteca as a Mexican native resource was of great interest to 91.7% of the respondents, allowing us to suggest that campaigns to highlight the importance of native ornamental plants that could be used to increase their knowledge, conservation and use in gardens and green areas in Mexico and abroad, looking for its sustainable use.
Keywords: bulbous; endemic species; sustainable marketing